2022
DOI: 10.1186/s12913-022-08525-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health-care provider experience of a person-centred, multidisciplinary, psychosocial support and harm reduction programme for patients with harmful use of alcohol and drug-resistant tuberculosis in Minsk, Belarus

Abstract: Background Tuberculosis (TB) often concentrates in groups of people with complex health and social issues, including alcohol use disorders (AUD). Risk of TB, and poor TB treatment outcomes, are substantially elevated in people who have AUD. Médecins sans Frontières and the Belarus Ministry of Health have worked to improve treatment adherence in patients with multi-drug or rifampicin resistant (MDR/RR)-TB and harmful use of alcohol. In 2016, a person-centred, multidisciplinary, psychosocial supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Lastly, social marginalization can exacerbate the situation ( 35 ). People struggling with alcohol or substance addiction may face stigmatization and lack of support, which can negatively impact their access to proper healthcare and their ability to engage in sustained TB treatment ( 32 , 35 , 36 ). Furthermore, alcohol and drug use disorders may contribute to diagnostic delays, leading to advanced disease at presentation and a higher risk of mortality ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, social marginalization can exacerbate the situation ( 35 ). People struggling with alcohol or substance addiction may face stigmatization and lack of support, which can negatively impact their access to proper healthcare and their ability to engage in sustained TB treatment ( 32 , 35 , 36 ). Furthermore, alcohol and drug use disorders may contribute to diagnostic delays, leading to advanced disease at presentation and a higher risk of mortality ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that patient-centered approaches have boosted adherence to treatment of TB and decreased ill health since the TB medication is prolonged (Horter et al, 2021). The tuberculosis patient-centered approach involves communication between patients and healthcare service providers (Harrison et al, 2022). The government of Tanzania, through the Ministry of Health, ensures the provision and access of free and quality health services to its citizen's through the use of digital technologies (Nahid et al, 2019;Neumark 2023).…”
Section: Introductionmentioning
confidence: 99%